Biventricular Impella placement via complete venous access. Issue 6 (22nd May 2017) - Kamioka, Norihiko; Patel, Ateet; Burke, Michael A.; Greenbaum, Adam; Babaliaros, Vasilis
Abstract : Impella (Abiomed, Danvers, MA) is an effective option for emergent treatment of critical refractory cardiogenic shock. However, in patients who have inadequate peripheral arterial access, Impella for left ventricular support sometimes requires surgical access, leading to disadvantages for emergent procedures or invasiveness for very sick patients. In addition, Impella for right ventricular support was recently reported to contribute to the management of severe biventricular dysfunction. In this report, we describe a case of refractory cardiogenic shock in a patient with inadequate vascular access who was treated with biventricular Impella via venous and caval‐aortic access under conscious sedation. This technique can be used as a bridge to surgical ventricular assist device or heart transplantation. © 2017 Wiley Periodicals, Inc.